La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Naviguer les attentes genrées de la communauté de danse swing de Montréal - Batty, Megan (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Gender and Extreme Metal: Understanding Gender Relations in the Montreal Extreme Metal Scene With Schippers' Gender Framework - Beauchamp, Caroline (Université Concordia, 2021)
Extreme metal is a masculine space, yet more and more women join in. They face a contradiction: as women, they are expected to adopt feminine behaviours; however, they are part of a subculture that valorizes warrior masculinity. I sought to understand the gender expectations of the Montreal extreme metal scene and interpret the contradictions encountered by women in this scene with the help of Schippers’ (2007) theoretical framework on gender. To do so, I conducted 16 individual interviews with women and men who take part in the scene. This research fills a gap in the literature on gender that derives from Connell and Schippers’ writings and addresses issues that the field of metal studies has brushed over. I found that metal men are the “default” participants in the scene. They are expected to be fine music connoisseurs and even become musicians. In contrast, women’s presence is heterosexualized and attributed to a romantic or sexual interest in metal men. Women are suspected of being “poseuses” or groupies with no real interest in the music until proven otherwise. To become legitimate participants, they have to overcome those expectations and prove that they are worthy of being viewed through the prism of masculinity rather than femininity. They do so by proving their exceptionality through manhood acts and distancing themselves from other women. Despite their gender transgressions, women’s presence does not fundamentally question gender relations but reaffirms the overall primacy of masculinity over femininity.

Énonciation, sexualités et genre en musique chez Philémon Cimon, Pierre Lapointe et Ariane Moffatt - Konaté, Khady (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Dans ce texte est proposée une « lecture du genre » (Boisclair 2002) des oeuvres de Philémon Cimon (L’été, Les femmes comme des montagnes), Pierre Lapointe (Pierre Lapointe, Sentiments humains) et Ariane Moffatt (Aquanaute, Le coeur dans la tête, Tous les sens). L’étude des chansons contenues sur ces albums prend pour point de départ une interrogation des subjectivités genrées de ces trois artistes, entre personne réelle et persona, et montre que ces dernières façonnent leurs compositions. La sollicitation du concept de sexe/genre ouvre dès lors la porte à l’exploration des représentations des identités sexuelles et de genre dans ces chansons, où les identités des artistes se trouvent mises en abîme. En s’intéressant à l’énonciation et au discours (en particulier, au discours amoureux) contenu dans le texte des chansons sélectionnées, il est possible de rendre compte de la reproduction des injonctions à l’hétérosexualité et des poncifs qui cloisonnent le genre, ainsi que des glissements et brouillages qui autorisent des resignifications du genre. Ainsi, chez Cimon, on observe la reconduite du point de vue masculin où la valeur du féminin réside dans sa capacité à émerveiller le sujet et à susciter son désir. À l’opposé, les textes de Lapointe et Moffatt dépeignent des personnages et des récits queer, bien que leur identité queer n’ait pas été revendiquée à l’heure de la parution de leurs oeuvres.

Genre, rap et enjeux de la visibilité dans l'espace public des rappeuses à Montréal : de la gestion de l'apparence physique pour être reconnue en tant qu'artiste - Lesacher, Claire (Les Cahiers de la Société québécoise de recherche en musique, 2021)

The Double Bind That Is Not a Bond: Cohen and Women - Pally, Marcia (From This Broken Hill I Sing to You: God, Sex, and Politics in the Work of Leonard Cohen, 2021)
Leonard Cohen's troubled relationship with God is here mapped onto his troubled relationships with sex and politics. Analysing Covenantal theology and its place in Cohen's work, this book is the first to trace a consistent theology across sixty years of Cohen's writing, drawing on his Jewish heritage and its expression in his lyrics and poems.Cohen's commitment to covenant, and his anger at this God who made us so prone to failing it, undergird the faith, frustration, and sardonic taunting of Cohen's work. Both his faith and ire are traced through: · Cohen's unorthodox use of Jewish and Christian imagery · His writings about women, politics, and the Holocaust · His final theology, You Want It Darker, released three weeks before his death.
Keywords: Music / General; Religion / Judaism / Theology; Religion / Theology

Gender and Embodiment in the Contemporary Montreal Swing Dance Community - Batty, Megan (Université McGill, 2020)
"This thesis explores embodiment and gender within the contemporary Montreal swing dance community. Drawing on scholarship in musicology, dance studies, jazz studies, and gender studies, I investigate the relationship between dancers and musicians/DJs. I explore the many facets of this choreomusical conversation and trace this dialogic and collaborative relationship on the social dance floor. The contemporary community is a product of the swing revival and navigating issues of authenticity thus becomes an important consideration for dancers, musicians, and DJs alike. One product of this revival is the set of heteronormative values that underpin the contemporary community. I investigate to what extent these values are reified, challenged, or altogether subverted by participants through musical and choreomusical choices. To this end I conducted interviews with six informants, each of whom has experience as both a dancer and musician and/or DJ. Their privileged position arising from their dual experience affords them insight on the ways in which dancers and musicians/DJs function within the community. This thesis builds on existing scholarship by situating the voices of individuals with choreomusical experience in dialogue with existing scholarship, and ultimately revalues the importance of both embodied knowledge and gender within the swing community"-- Author's abstract

Imaginary Women, Imaginary Audience: Gender and Top 40 Radio in Montréal - Maki, Christine (Women in Radio: Unfiltered Voices from Canada, 2020)
Though they no longer call themselves Top 40, popular music radio stations remain present on the dial today, complete with loud, mostly male DJs, hoping to attract a mainly female audi ence. Using the talk on two Montréal music stations, which hire mainly male announcers who select music assumed to fit wom en’s tastes, Christine Maki examines the continuing perception that women’s voices aren’t low or authoritative enough and that emotional issues prevent them from presenting difficult news stories. Her conclusion: the overall medium remains relatively unchanged over the decades, despite massive evolution in the wider media landscape.

The “Manic Pixie Dream Girl of the Synth-Pop World” and Her “Baby Doll Lisp”: Grimes and the Disabling Logics of the Feminization and Infantilization of Lisping - Holmes, Jessica A. (Journal of Popular Music Studies, 2019)
Audible in speech and song, electro-pop singer Grimes’s so-called “baby doll” lisp generates endless buzz online, ranging from light-hearted adoration, to infantilization, to sexual fetish and even to ableist, misogynist anti-fandom. This article uses the reception of her lisp to build an intersectional theory of lisping across its medical and socio-cultural constructions, bridging work in disability studies, dysfluency studies, voice studies, and popular music studies in the process. I situate the slippage between adoring, infantilizing, fetishistic, and violent characterizations of Grimes’s lisp as reflective of the infantilization of “communicative disorders” in speech language pathology, and the dysfunction associated with feminine coded-speech patterns (e.g. vocal fry and up talk) in the popular imaginary. Lisping is profitably understood as an audible form of “liminal” difference relative to visible physical disabilities (St. Pierre), and to certain ableist, gendered, and racialized conceptions of normative vocality. Ultimately, in the English-speaking world, the lisp is symbolically-coded feminine while exceeding the norms of female vocality, thereby giving rise to a polarizing set of associations that work against female authority and, by extension in Grimes’s case, female musical authorship. Grimes’s reception thus offers a valuable case study for interrogating how misogynist fantasies regarding femininity are thought localized in the female voice, and the symbolic ties between disability and femininity.

Women in Leonard Cohen's Work - Álvarez Pérez, Maria Icíar (Multidisciplinary Views on Popular Culture: Proceedings of the 5th International Selicup Conference, 2014)

Le voyage, la danse et la représentation des femmes dans la culture de grande consommation (1936-1947) - Savoie, Chantal (Les Cahiers de l'IREF, 2014)

Construire le corps, construire la star : une agentivité à l'œuvre dans deux clips de Marie-Mai - Labrosse, Claudia; Melançon, Johanne (Chanson et performance. Mise en scène du corps dans la chanson française et francophone, 2013)
La moustache de Georges Brassens, la robe noire d’Edith Piaf, les paillettes de Claude François, les cheveux de Dalida… Les chanteurs ont un corps indissociable de leurs chansons, et ce livre s’intéresse précisément à la présence physique de la musique populaire, à sa performance sur scène et sur disque. Si le dualisme historique entre le corps et l’esprit a eu tendance, en France, à inluencer la réception de la chanson en attribuant plus de prestige à la modestie d’un Brassens qu’à la séduction démonstrative d’un chanteur de ‘variétés’, cet ouvrage est l’occasion de revenir sur cette opposition et de la nuancer, en identiiant les artistes qui ont su l’ignorer ou la contester. En légitimant l’étude de la performance (au sens de mise en scène du corps), cette étude met sur un pied d’égalité des genres aussi différents que la chanson ‘à textes’, le rock, le disco, le zouk ou le cabaret, et recadre les études sur la chanson loin de l’analyse de paroles. Il démontre, notamment, qu’en tant que véhicule de la chanson, le corps du chanteur reflète des a priori sociaux sur les rapports entre physique et séduction, genre et sexualité, apparence ethnique et identité, artiice et authenticité. Cet ouvrage est le fruit d’une collaboration entre chercheurs de GrandeBretagne, des États-Unis, du Canada, de Nouvelle-Zélande et de France, et dont la qualité commune est une fraîcheur d’analyse pluridisciplinaire inspirée des études culturelles. Observant les corps de chanteurs et chanteuses en France, aux Antilles et au Québec, ce livre offre une rélexion comparatiste sur les codes esthétiques en vigueur dans chaque contexte national, et observe les tensions sociales, sexuelles et identitaires qui sous-tendent la performance musicale.

La chanson à succès dans les années 1940. Une modernité culturelle par acclamation ? - Savoie, Chantal (Globe, 2013)
Dans le contexte de travaux plus larges portant sur l’histoire de la chanson à succès par l’analyse des préférences musicales des lectrices du Bulletin des agriculteurs dans les années 1940, nous nous intéressons ici aux éléments qui permettent de comprendre les modalités par lesquelles les goûts musicaux témoignent de l’émergence d’une modernité culturelle au Québec dans les années 1940. Deux postulats orientent notre perspective. Le premier consiste à supposer l’existence d’une modernité culturelle « populaire » qui transite par la forme, les supports et la technologie. Le second sonde la façon dont les thèmes intimes et la focalisation sur l’expression du sentiment amoureux marquent une transformation des valeurs et, surtout, explore les marques formelles et discursives qui portent ces valeurs dans la chanson à succès. , As part of a larger research project on the history of popular song, which analyzes the musical preferences of the female readers of the Bulletin des agriculteurs in the 1940s, this article focuses on those elements that allow for an understanding of the modalities by which these women’s musical tastes reflected the emergence of a cultural modernity in Quebec during that decade. Two basic premises orient my perspective on the subject. The first presupposes the existence of a “popular” cultural modernity based on form, equipment, and technology. The second explores both the way in which intimate themes and the importance given to expressions of love reflected a shift in values, as well as the formal and discursive markers that transmitted these values in popular song.

De la cuisine au studio - Lupien, Anna (Éditions du remue-ménage, 2012)
De la cuisine au studio explore les parcours de douze artistes issues de trois générations différentes : femmes signataires du manifeste Refus global en 1948, premières cinéastes qui ont œuvré à l’ONF dans les années 1970 et artistes médiatiques impliquées au Studio XX. À partir d’entrevues avec les artistes, Anna Lupien pose un regard sociologique sur l’expérience de créatrices qui ont investi l’art en tant qu’espace d’expression dans la sphère publique. De quelle façon ont-elles élaboré des stratégies créatives et par le fait même donné corps à des transformations sociales engendrées par le mouvement féministe, notamment en ce qui a trait à la conciliation travail-famille ? Comment ont-elles intégré des milieux artistiques qui ne leur étaient pas ouverts d’emblée ? Comment se sont-elles engagées pour le bien commun à travers leur parcours artistique ? Les histoires de ces artistes – Madeleine Arbour, Christine Brault, Mireille Dansereau, Dorothy Todd Hénaut, Stéphanie Lagueux, Bérengère Marin-Dubuard, Helena Martin Franco, Terre Nash, Anne-Claire Poirier, Françoise Riopelle, Bonnie Sherr Klein et Françoise Sullivan – témoignent des luttes inachevées du mouvement féministe et des brèches qu’elles ont pratiquées dans l’ordre des choses, suscitant des rencontres originales entre l’art et le politiqu

Sociologie et vecteurs de la popularité : l'mpact de la réception féminine sur la chanson québécoise des années 1940 - Savoie, Chantal (25 ans de sociologie française de la musique en France. Réflexivité, écoutes, goûts, 2012)

De la cuisine au studio : le rapport public/privé interrogé au fil des parcours d'artistes québécoises de trois générations - Lupien, Anna (Université du Québec à Montréal, 2011)

Chansons de travail, chansons de chômage : une lecture du monde ouvrier pendant la crise à travers l’œuvre de La Bolduc - Charest, Marie-Josée (Études littéraires, 2009)
In the 1930s, Mary Travers wrote folk songs dealing with the thorny issue of the working poor during hard times. A self-styled “woman at the service of the community”, she focused on those who lost their jobs as a result of the economic crisis. Heeding tradition, she lauded the work of famers whom she perceived as the mythical representatives of an idealised “old era”. How did she reconcile her songs praising tradition with an increasingly industrial labour market ? How did she react to women entering the workforce ? What did she think of government actions in the face of dwindling employment and pressing poverty ? Did she consider herself to be a career woman, what with hers being the first successful recordings of Quebec folk songs ? Confronting or buttressing established taboos such as those about women in the workforce, she wrote songs reflecting those societal issues prevalent at the time. Yet, she set herself apart both through her trade as a songwriter and her depiction of it. The economic situation in the province of Quebec influenced how labour was perceived, and her writings, favouring the standpoint of a working woman from the lower classes where employment is a matter of both survival and pride, echoed this perception with originality. A sociological and critical analysis of her songs illustrates the societal discourse on labour that prevailed during hard times.

Les représentations de la femme dans l'œuvre scénique de Diane Dufresne, 1975-1984 - Lafrenière, Marilyne (Université du Québec à Trois-Rivières, 2008)
Ce mémoire de maitrise vise a identifier les representations de la femme proposees par la chanteuse Diane Dufresne entre 1975 et 1984, afin de mettre en lumiere la contribution d'une artiste individuelle et officiellement non-engagée au discours public du Quebec de ces annees. Les deux dimensions de la communication - remission et la reception - y sont traitees et comparees. Une analyse thematique des paroles des chansons de Diane Dufresne, mise en relation avec differents aspects de ses mises en scene, nous ont permis de cerner l'univers de Partiste ainsi que les modeles feminins qu'elle propose. II s'agit de femmes solitaires, instables, sexuelles, sensuelles, parfois agressives et generalement apeurees face au monde dans lequel elles evoluent. Ainsi, les diverses origines du malaise existentiel des heroines - le quotidien lassant, la vitesse, le stress, les normes sociales, la vieillesse et la dictature de 1'image - sont autant d'entraves ressenties dans leur quete de liberte et de critiques adressees au monde contemporain. Leurs attaches sont d'ordre familial et professionnel. Les heroines embrassent egalement deux causes: la protection de Penvironnement et la liberte d'expression. Cette derniere - par la creativite qu'elle implique — est presentee comme un exutoire efficace au mal de vivre. Les heroines incarnees par Diane Dufresne s'inscrivent en marge des modeles generalement diffuses dans la chanson des decennies 1970 et 1980. L'etude de la presse culturelle quebecoise et des entrevues avec des fans de Partiste nous renseignent sur la reception de Diane Dufresne et de son oeuvre dans la societe ou elles sont diffusees. Etonnamment, les journalistes et les fans ne se sont pas averes etre des recepteurs si distincts. En effet, s'ils commentent parfois aprement la vie personnelle de Diane Dufresne, son comportement hors de la scene ou ses prises de position face a l'industrie, l'apparente fascination des journalistes en regard de l'art de Diane Dufresne les situe plus pres d'un public d'admirateurs que de la critique. C'est avec complaisance, sauf quelques rares exceptions, que les journalistes ont relaye 1'image que Diane Dufresne voulait donner d'elle-meme. Cette image est neanmoins incomplete puisque la douceur et la conscience sociale de Partiste y sont amenuisees par rapport aux autres dimensions de sa persona. Les journalistes culturels ont aussi contribue a creer une autre dimension au personnage public qu'est Diane Dufresne qu'ils associent a P emancipation feministe, alors qu'elle-meme refusait clairement cette etiquette. Alors que Paspect feministe est evacue du discours des fans, la force de Paffirmation de Diane Dufresne, voire son emancipation individuelle persiste et constitue un des piliers de leur attachement fidele et constant à l'artiste. Leur identification profonde a Diane Dufresne, la specificite qu'elle reconnait a chaque spectateur et Pinvitation qu'elle lance a chacun d'assumer sa difference lors de ses spectacles scelle le lien entre l'artiste et son public.

The conservation of a gender fantasy: women and Top 40 radio in Montreal - Maki, Christine (Université McGill, 2008)
This work examines today's Anglophone Top 40 radio in Montreal in terms of gender. Looking at the history of commercial radio, and the historical relationship between radio and women, it argues that these radio stations have always programmed based on an imagined rather than actual understanding of their target audience. Programmers today continue to hold a conservative understanding of their female audience and their interests, and to program using a stereotypical understanding of gender.

Lire Mary Travers (La Bolduc). Chansons et représentations sociales dans le Québec des années 1930 - Charest, Marie-Josée (Université de Montréal, 2007)
Ce mémoire de maîtrise intitulé Lire Mary Travers (La Bolduc). Chansons et représentations sociales dans le Québec des années 1930 a pour objet les dimensions sociales, historiques et idéologiques que les textes de La Bolduc prennent en écharpe et transforment. S'intéressant à la totalité des chansons écrites par Mary Travers entre 1927 et 1939, l'étude offre une analyse détaillée de la représentation de la société québécoise de l'entre-deux-guerres portée par son œuvre. C'est par le bais de l'analyse littéraire, de la cantologie et de la sociocritique que ces chansons humoristiques racontant la vie quotidienne et la misère des petites gens sont interprétées. Une attention particulière est portée au genre « chanson », à la narrativité, au registre linguistique, à l'humour, à la représentation des femmes et aux dérives idéologiques observées dans son répertoire. Par l'étude des chansons énumératives, des dialogues chantés et des autres ballades créées par Mary Travers, le mémoire rend compte de la mesure de l'inscription sociale de l'écriture de cette chansonnière et folkloriste populaire.

Keeping Time with Lesbians on Ecstasy - Halberstam, J[ack] (Women and Music: A Journal of Gender and Culture, 2007)

La réception féminine de la chanson sentimentale populaire - Savoie, Chantal (Le féminin, le masculin et la musique populaire d'aujourd'hui. Actes de la journée du 4 mars 2003., 2005)

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation m the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.